METHOD OF MULTIPLE RECALCULATIONS. - O.I. Vejtsblit (Kherson State University, 2010)
In this work for the analysis of results of integration it is offered a posteriori method of multiple recalculations which is a generalization of a Runge - Richardson method of double recalculation.